A Density Functional Study of Au Clusters Adsorbed on Si(001): Formation of Cluster Lattice and a Transition From Non-Metallicity to Metallicity - Bose, Rudra Prasad; Chakrabarti, Kisalaya (International Journal of Computer Sciences and Engineering, 2025)
Electronic structure calculations are carried out under the density functional formalism for understanding the structure and energetic of gold atoms and gold clusters containing up to four atoms adsorbed on the Si(001) surface. The stable adsorption sites of gold atoms and the gold clusters on the Si(001):p(2x1) surface and the structural change of the clusters due to their interaction with the surface are presented. Also, the adsorption of Au clusters on Si((001):p(2x1) in presence of defects are studied. However, most significant finding of our calculations is that the formation of Au3 cluster lattice on the Si(001) is possible and, as a consequence, the Si(001) surface becomes metallic.